Human Needs for Dakwah (The Existence of KODI as the Capital's Da'wah Organization) - Abdul Hamid; Badrah Uyuni (TSAQAFAH, 2023)
Dakwah is an invitation to implement religion in everyday life whose primary object is humans. Humans are essentially forgetful creatures, so they need dakwah. The Qur'an sees the forgetfulness inherent in human identity as a holy and perfect creature. Dakwah is a noble task for Muslims. Da'wah activities will be significantly helped if supported by many parties, including the local government. And KODI, as a non-regional institution in the religious field, has contributed to dakwah activities, especially in the city of Jakarta. This research intends to examine. The strategic function of KODI is as an organizer of da'wah for the benefit and welfare of the people of DKI Jakarta. KODI has a role in increasing the coordination, synchronism, and dynamism at the institution of propagation in the DKI Jakarta, as an effort to apply the reality of ideology Moslem in the institution of government. This study uses a qualitative method. By using a descriptive approach. Data collection techniques using observation, interviews, and documentation studies. Research result illustrates that KODI's dakwah routinely holds Muballigh Cadre Training (PKM) in answering dakwah issues: the problems of community dakwah in the capital city of Jakarta, which is increasingly diverse and complex, both from social and psychological problems.